Analisis Kinerja PPAIW dalam Penegakan Hukum Wakaf Tanah di Indonesia - Islamiyati, Islamiyati; Musyafah, Aisyah Ayu; Ardani, Mira Novana; Widanarti, Herni (Law, Development and Justice Review, 2024)
PPAIW has the main task of providing waqf administration and serving the needs of prospective wakif who will donate their assets by following per under the provisions of the legislation. The purpose of the PPAIW is so that the community gets authentic evidence that waqf has occurred. The existence of PPAIW makes waqf law change from a law that lives in the community to a written law that must be recorded by the state. However, that reality shows that PPAIW's performance in enforcing waqf law has not met the standards. The purpose of this study is to analyze the performance of PPAIW in enforcing the waqf law and formulate efforts that can be made in enforcing the waqf law. This research uses the empirical juridical method with qualitative analysis. PPAIW's performance in enforcing waqf law in Indonesia has not been by following per under good work indicators, because there are several legal problems in carrying out their obligations, so their performance is not up to standard. Efforts must be made to enforce waqf law, namely; increase PPAIW resources; realize a corruption-free government, and KKN; provide good service (good governance); guard nadzir in the land registration process; provide a decree for the appointment of nadzir; empowering nadzir and the community; mastering dispute resolution mechanisms and advocating for the community; comfortable office atmosphere and support PPAIW performance.